SRI RAHMAYANTI EFEKTIVITAS PROGRAM KARTU TANI TERHADAP KESEJAHTERAAN MASYARAKAT PETANI DI DESA BULO KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG: THE EFFECTIVENESS OF THE FARMERS CARD PROGRAM ON THE WELFARE OF FARMING COMMUNITIES IN BULO VILLAGE, PANCA RIJANG SUB-DISTRICT, SIDENRENG RAPPANG DISTRICT - rahmayanti, sri (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Bulo Village, Panca Rijang District is one of the areas that has started to apply the farmer card policy, the problem that occurs is that there are still farmers who do not have farmer cards in Bulo Village, then there are still people who have farmer cards but are not yet active, so it needs to be activated independently. by farmers, the aim is to find out how the effectiveness of the farmer card program is in Bulo Village. The location of this research will be carried out in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency. This study has two variables, the X variable, namely the Effectiveness of the Farmer's Card Program, and the Y variable, namely Community Welfare. Population and sample data analysis techniques that will be carried out using the SPSS program assistance. There are 86 respondents, 7 people who answer very well with a total percentage of 8.13%, respondents who answer well there are 17 people with a total percentage of 19.76%, respondents who answer less well there were 40 people with a total percentage of 46.51%, respondents who answered not well there were 10 people with a total percentage of 11.62%, and respondents who answered very badly there were 12 people with a total percentage of 13.95%. The average percentage obtained based on the table above is 58% in the "Not Good" category. The percentage value of the program effectiveness indicator in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency is 58% in the unfavorable category. The percentage value of the community welfare indicator in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency, 64% were in the good category. The influence between program effectiveness and community welfare in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency was 45.2%, categorized as "Influential/Significant".